Outward Bound Instructors' Experience of Stress: Storms, Students, and Role Strain. (June 2022) - McGovern, Gina
Background: Outward Bound (OB) provides experiential outdoor learning programs where students grow through overcoming challenges. Instructors leading these wilderness courses face numerous demands and situational conditions which may create stress.Purpose: This study sought to describe instructors' experience of stress on OB courses with adolescents.Methodology/Approach: In semi-structured interviews, 31 OB instructors from two sites provided in-depth guided narratives of highly stressful course situations, which were analyzed using grounded theory methods.Findings/Conclusions: Findings indicated that instructors were stressed by unsafe and unpredictable situations (e.g., adverse weather, dangerous terrain, medical concerns) and student behavior, thoughts, and feelings (e.g., conflict, oppositional behavior, distress). Analysis also suggested that the internalization of role demands—for student safety, student learning, and control—intensified experiences of stress. Self-perceptions of failure to meet these role demands led to role strain. In addition, stress affected instructors' functioning and their interactions with students.Implications: This study suggested several recommendations for OB and other youth-serving organizations. These include assessing the amount and types of stress instructors are experiencing on a regular basis and examining how these stressors might be reduced or mitigated by actors at multiple levels in the organization.